On the Occasion of the Seventieth Birthday of Professor Guo Boling (Journal of Partial Differential Equations, 2007)
Professor Boling Guo, Academician of Chinese Academy of Sciences, born on October 23, 1936, in Longyan, Fujian, China, is now working in Beijing Institute of Applied Physics and Computational Mathematics (IAPCM). After four years' studies, he graduated from the department of mathematics, Fudan University in September, 1958. He was an assistant professor of this department after his graduation until January, 1963 when he joined the institute which he is now working in. He was first an assistant professor from February, 1963, to October, 1982, in IAPCM, then an associate professor from December, 1982, to October, 1987, and finally a professor from October, 1987 up to now. Professor Guo began to supervise Ph.D students in 1990.